Pelatihan Pembuatan Konten Promosi Untuk UMKM Fashion di Cibinong, Kabupaten Bogor: Penggunaan Canva dan Reels untuk Meningkatkan Daya Tarik Visual Produk - Kushariyadi, Kushariyadi; Awaludin, Dipa Teruna; Nurhayati, Siti Annisa Wahdiniawati; Sitinah, Sitinah; Purwoko , Bambang (Jurnal Pengabdian Kepada Masyarakat Kalam, 2024)
In the visually driven digital era, compelling promotional content is vital for the sustainability and growth of Micro, Small, and Medium Enterprises (UMKM), particularly in the aesthetic-dependent fashion sector. However, many fashion UMKM actors, especially at the local level, like Cibinong, Bogor Regency, face limitations in creating professional promotional content that can attract online consumers. A lack of skills in visual design and the utilization of dynamic social media features often hinders their ability to enhance product appeal. This community service activity aimed to address this issue by providing training in promotional content creation, focusing on the use of the intuitive Canva platform and the Reels feature on social media to enhance the visual appeal of fashion UMKM products in Cibinong, Bogor Regency. The training employed a participatory and educative approach, involving practical sessions on Canva design principles and Reels video creation tailored for fashion products. Participants, consisting of local fashion UMKM owners, actively engaged in creating promotional materials for their businesses. Preliminary observations and post-training assessments indicated an increased understanding and ability among participants to produce more visually engaging content. This initiative demonstrated the potential of accessible digital tools and targeted training in empowering local fashion UMKM to improve their online presence and marketing effectiveness.